Effects of health insurance on patient demand for physician services - Jerome Dugan (Health Economics Review, 2020)
Background: In recent years, policymakers have sought to reduce health disparities between the insured and uninsured through a federal health insurance expansion policy; however, disparities continue to persist among the insured population. One potential explanation is that the use of healthcare services varies by the type of health insurance coverage due to differences in the design of coverage. The aim of this study is to examine whether health insurance coverage type is associated with the structure and use of healthcare services. Methods: The nationally representative Medical Expenditure Panel Survey and multinomial logistic regression are used to estimate the effects of different types of health coverage on the combinations of routine and emergency care sought and received. Results: The multinomial logistic regression analysis for the overall sample revealed privately insured respondents reported higher use of routine care only p < 0.01 and lower use of emergency room care only (- 2.13%; p < 0.01) than the uninsured. The publicly insured reported similar trends for use of routine care only (17.93%; p < 0.01) as the privately insured, as compared to the uninsured. Both the privately and publicly insured reported higher use of a mixture of care; however, publicly insured were more likely to use a mixture of care (8.57%, p < 0.01). Conclusion: The results show that health insurance is associated with higher use of the physician services, but does not promote the use of cost-effective schedules of care among the publicly insured.
Keywords: 330; Healthcare management; Chronic disease; Health insurance